Pokemon: bye, bye butterfree - Muldrow, Diane (New York : A Golden Book, 1998)
Trouble's in the air! It looks like Team Rocket may pull off their evil scheme this time - stealing the Butterfree as they cross the ocean.
Keywords: Adventures -- Fiction; Children stories -- Fiction